An analysis of cigarette prices and affordability in Africa: evidence from African Cigarette Prices (ACP) Data - Chinembiri, Tapiwa (School of Economics, 2019)
Cigarette affordability is defined as the amount of money or its time equivalent required to purchase cigarettes. It is one of the important determinants of tobacco consumption and is calculated from the interaction of consumer income and cigarette price. Governments of Low- and Middle-Income Countries have generally underutilized the most powerful tool in tobacco control, namely decreasing tobacco affordability by increasing tobacco taxes. I analyze price data collected from retail outlets and street vendors in seven countries: Botswana, Lesotho, Mauritius, Namibia, South Africa, Swaziland, and Zimbabwe. I use the African Cigarette Prices dataset [n=9285], which has data collected in June and July 2016. Affordability is expressed as Relative Income Price (RIP), i.e., as a percentage of per capita GDP for all countries. For South Africa, affordability is also estimated separately using household per capita income by sub-national region. The results of the study show that cigarettes are more affordable in countries and provinces where incomes are high. I compare the differences in prices between cigarette brands, packaging, and outlet type across countries, and, in South Africa's case, across provinces. The study is relevant as it indicates that, when setting excise taxes, policy makers should also take cigarette prices and incomes into account.